ROUTINE ACTIVITIES AND BURGLARY IN STUDENTS’ OFF- CAMPUS SETTLEMENTS AT THE FEDERAL UNIVERSITY WUKARI, TARABA STATE - Ahmadu, Abubakar; Valentine Onyegbulem, Emeka (African Journal of Social and Behavioural Sciences, 2026)
Over time, students in Nigeria’s tertiary institutions have resorted to off-campus accommodation due to limited on-campus hostel accommodation. Off-campus settlements are a mosaic, housing students from various ethnic, religious and social groups, thereby creating fertile ground for heightened routine activities that predispose students to burglary. This study explored gaps in existing research by focusing on students’ routine activities, their patterns, and their overall implications for burglary. Using the broken windows theory and routine activity theory, the study examined the variables that account for students’ exposure to burglars. The survey design was adopted given its effectiveness in collecting data from a sample of the population for generalisation. Cochran’s sample size formula was used to select 131 students from a sample frame. A multistage sampling technique screened students across clusters of settlements, using a systematic approach to have students complete a closed-ended questionnaire in their homes. Frequencies, percentages, mean and standard deviation were used for descriptive analysis. Students’ nighttime activities were found to be the most strongly associated with burglary. Additionally, most burglaries occurred during holidays, although there were troubling cases in which students went out for studies and other engagements at night, including attending lectures in broad daylight. Accessories such as laptops, radios, and televisions were the most frequently stolen items during the holidays. The multiple linear regression results showed F [(2, 117) =6.419, P=0.002], suggesting a significant effect of the pattern of routine activities on burglary. Also, the Pearson correlation results revealed a significant overall relationship between students’ routine activities and burgled items. The study recommends, among other measures, that university management and landlords work together to ensure security, with landlords recruiting security guards and the University security unit monitoring off-campus settlements.